Idealism in Educational Philosophy: Reclaiming Values in an Age of Scientific Pragmatism - Mubin, Hakun; Nasrowi, Bagas Mukti; Hufron, M (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Education, as a means of shaping humanity through human resource development, demands a comprehensive outlook that encompasses the full spectrum of human existence and potential. Addressing contemporary educational challenges requires more than practical experience; it necessitates critical thinking, rigorous scientific analysis, and sustained scholarly research. Additionally, education must be firmly grounded in philosophical discourse and reflective inquiry. As the foundational discipline underlying all sciences, philosophy seeks to resolve both existing and emerging human challenges, particularly those concerning the metaphysical triad of God, humanity, and nature. However, with the ongoing evolution of society and the acceleration of technological change, many contemporary issues have surpassed the explanatory capacity of traditional philosophy alone, leading to the emergence of empirical science as a complementary approach to understanding reality. The term